T-cell responses induced by ChAdOx1 nCoV-19 (AZD1222) vaccine to wild-type severe acute respiratory syndrome coronavirus 2 among people with and without HIV in South Africa - McMahon, WC; Kwatra, G; Izu, A; Koen, AL; Greffrath, J; Fairlie, L; Patel, F; Mukendi, CK; Mbele, NJ; Lala, R; Burgers, WA; Nunes, MC; et al. (Wolters Kluwer, 2023)
Objective(s): This study aimed to investigate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific T-cell responses 14 days after single-dose ChAdOx1 nCoV-19 (AZD1222) vaccination in black Africans with and without HIV in South Africa, as well as determine the effect of AZD1222 vaccination on cell-mediated immune responses in people with HIV (PWH) with prior SARS-CoV-2 infection. Methods: A total of 70 HIV-uninfected people and 104 PWH were prospectively enrolled in the multicentre, randomized, double-blinded, placebo-controlled, phase Ib/IIa trial (COV005). Peripheral blood mononuclear cells (PBMCs) were collected from trial participants 14 days after receipt of first dose of study treatment (placebo or AZD1222 vaccine). T-cell responses against the full-length spike (FLS) glycoprotein of wild-type SARS-CoV-2 and mutated S-protein regions found in the Alpha, Beta and Delta variants were assessed using an ex-vivo ELISpot assay. Results: Among AZD1222 recipients without preceding SARS-CoV-2 infection, T-cell responses to FLS of wild-type SARS-CoV-2 were similarly common in PWH and HIV-uninfected people (30/33, 90.9% vs. 16/21, 76.2%; P = 0.138); and magnitude of response was similar among responders (78 vs. 56 SFCs/106 PBMCs; P = 0.255). Among PWH, AZD1222 vaccinees with prior SARS-CoV-2 infection, displayed a heightened T-cell response magnitude compared with those without prior infection (186 vs. 78 SFCs/106 PBMCs; P = 0.001); and similar response rate (14/14, 100% vs. 30/33, 90.9%; P = 0.244). Conclusion: Our results indicate comparable T-cell responses following AZD1222 vaccination in HIV-uninfected people and PWH on stable antiretroviral therapy. Our results additionally show that hybrid immunity acquired through SARS-CoV-2 infection and AZD1222 vaccination, induce a heightened T-cell response.